Study on the Control Effect of Borehole Gas Extraction in Coal Seams Based on the Stress–Seepage Coupling Field - Hongsheng Wang; Huaming An; Bingbing Yang (Fire)
In order to determine the reasonable parameters of high-gas and extra-thick coal seam drainage, considering the factors of the coal seam metamorphic degree, stress condition, gas occurrence state, and permeability dynamic change, the gas desorption, diffusion, and transport process of coal seam gas are analyzed. A secondary distribution model of coal around the borehole, a porosity variation model of coal around the borehole, a stress–seepage coupling model, a pore flow model of the pressure-driven transition flow zone, and a free molecular flow zone are established. Taking the gas drainage of Zhangcun Coal Mine of Lu’an Group as the research object, the influence of drilling hole diameter, coal seam permeability, gas original pressure, and other factors on the control range of coal seam drainage drilling is simulated by ANSYS Fluent 6.3.26. The results show that secondary stress distribution occurs in the coal seam drill hole under the action of lead stress, which leads to the change in porosity; the seepage zone, transition zone, molecular flow zone, and original rock stress zone are presented around the drill hole; and the range of influence of the drill hole is mainly based on the seepage zone and the transition zone, supplemented by the molecular flow zone. The control range of the drill hole is in a positive proportional relationship to the diameter of the drill hole, the porosity of the coal seam, and the original pressure of the gas.